2020
DOI: 10.1038/s41598-020-58105-4
|View full text |Cite
|
Sign up to set email alerts
|

Retrospective analysis of patients with non-tuberculous mycobacteria from a primary hospital in Southeast China

Abstract: to achieve a comprehensive understanding of the characteristics of patients with non-tuberculous mycobacteria (NTM), patients with NTM between January 2016 and June 2019 were recruited from a primary hospital. NTM were identified based on the MBP64 protein assay. The clinical records and laboratory assay results were retrospectively reviewed. A total of 204 patients with NTM were included in the final analysis. The patients with multiple isolations were more likely accompanied with chronic obstructive pulmonar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 35 publications
3
5
0
Order By: Relevance
“…Among patients with NTM in this study, the patients with COPD were mainly older and males, as it was also previously reported [11]. Limited data are available regarding the in uence of NTM infection on COPD, but our previous work and another study suggested that repeated isolation of samples in patients was associated with a higher percentage of COPD [10,11]. In a follow up study, COPD patients with NTM-positive sample more likely experience exacerbation than those with NTM-negative samples, and patients with multiple positive samples had a more pronounced pulmonary function decline than those with single or no positive samples [22].…”
Section: Discussionsupporting
confidence: 78%
See 4 more Smart Citations
“…Among patients with NTM in this study, the patients with COPD were mainly older and males, as it was also previously reported [11]. Limited data are available regarding the in uence of NTM infection on COPD, but our previous work and another study suggested that repeated isolation of samples in patients was associated with a higher percentage of COPD [10,11]. In a follow up study, COPD patients with NTM-positive sample more likely experience exacerbation than those with NTM-negative samples, and patients with multiple positive samples had a more pronounced pulmonary function decline than those with single or no positive samples [22].…”
Section: Discussionsupporting
confidence: 78%
“…The percentage of tuberculosis history between patients with COPD or without COPD was not signi cantly different, suggesting that previous tuberculosis infection might not be associated with the pathogenesis of COPD. Previous works showed that the percentage of patients with bronchiectasis presenting multiple NTM positive isolations is comparable to the percentage of patients with bronchiectasis presenting a single NTM positive isolation [10,11], indicating the limited impact of NTM infection on bronchiectasis. Instead, repeated isolations of NTM positive strains partly contributes to the progression of COPD [10,11].…”
Section: Discussionmentioning
confidence: 94%
See 3 more Smart Citations